THE NEED FOR DIRECT OBLIGATIONS FOR BUSINESSES ON THE INTERNATIONAL TREATY ON BUSINESS AND HUMAN RIGHTS: AN ANALYSIS OF THE INTER-AMERICAN SYSTEM OF HUMAN RIGHTS CASE LAW - Oliveira Soares, Andressa; Carneiro Roland, Manoela; Fernandes Maso, Tchenna (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2025)
This article is part of the discussion of human rights and business from the perspective of the accountability of companies, especially transnational corporations, within the framework of the debates on binding standards in international law. In the last eight years, the United Nations Human Rights Council (UNHRC) has discussed the construction of a legally binding instrument on transnational corporations and human rights, within the Open-ended Intergovernmental Group for the construction of the instrument created by Resolution 26/9. The negotiations have been marked by an intense dispute over the normative content. One of them is the possibility or not of implementing direct obligations for companies. Simultaneously, the Inter-American System of Human Rights issued a report on the Inter-American Standards on Business and Human Rights. Seeking to contribute to the discussions taking place at the UNHRC, this paper presents empirical research that aims to answer the following question: are there any standards in international human rights law, especially in the Inter-American System of Human Rights, that provide a substrate for the provision of direct obligations for businesses in the legally binding instrument? The methodology for constructing the article follows the inductive approach and uses literature review and documentary analysis. The results show that it is not only possible but also extremely necessary for the effectiveness of the international instrument to insert direct obligations for transnational corporations in the document.